Increased amygdala reactivity following early life stress: a potential resilience enhancer role. Issue 1 (December 2017) - Yamamoto, Tetsuya; Toki, Shigeru; Siegle, Greg; Takamura, Masahiro; Takaishi, Yoshiyuki; Yoshimura, Shinpei; Okada, Go; Matsumoto, Tomoya; Nakao, Takashi; Muranaka, Hiroyuki; Kaseda, Yumiko; Murakami, Tsuneji; et al.
Abstract Background Amygdala hyper-reactivity is sometimes assumed to be a vulnerability factor that predates depression; however, in healthy people, who experience early life stress but do not become depressed, it may represent a resilience mechanism. We aimed to test these hypothesis examining whether increased amygdala activity in association with a history of early life stress (ELS) was negatively or positively associated with depressive symptoms and impact of negative life event stress in never-depressed adults. Methods Twenty-four healthy participants completed an individually tailored negative mood induction task during functional magnetic resonance imaging (fMRI) assessment along with evaluation of ELS. Results Mood change and amygdala reactivity were increased in never-depressed participants who reported ELS compared to participants who reported no ELS. Yet, increased amygdala reactivity lowered effects of ELS on depressive symptoms and negative life events stress. Amygdala reactivity also had positive functional connectivity with the bilateral DLPFC, motor cortex and striatum in people with ELS during sad memory recall. Conclusions Increased amygdala activity in those with ELS was associated with decreased symptoms and increased neural features, consistent with emotion regulation, suggesting that preservation of robust amygdala reactions may reflect a stress buffering or resilience enhancing factor against depression and negative stressful events.